2010
DOI: 10.1111/j.1365-294x.2010.04553.x
|View full text |Cite
|
Sign up to set email alerts
|

History vs. habitat type: explaining the genetic structure of European nine-spined stickleback (Pungitius pungitius) populations

Abstract: The genetic structure of contemporary populations can be shaped by both their history and current ecological conditions. We assessed the relative importance of postglacial colonization history and habitat type in the patterns and degree of genetic diversity and differentiation in northern European nine-spined sticklebacks (Pungitius pungitius), using mitochondrial DNA (mtDNA) sequences and 12 nuclear microsatellite and insertion/deletion loci. The mtDNA analyses identified - and microsatellite analyses support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
180
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 110 publications
(209 citation statements)
references
References 84 publications
(159 reference statements)
28
180
1
Order By: Relevance
“…These results align with the interpretation that populations in finite and often very small freshwater habitats exhibit smaller effective population sizes than those living in marine habitats where populations are also connected by at least occasional gene flow. It is noteworthy that the polarized patterns of genetic variability and differentiation in freshwater vs marine habitats cannot be explained by biased representation (e.g., differences in key life history traits influencing genetic variability) of species in each of these groupings; similar results are seen when populations of the same species residing in freshwater and marine habitats are compared (Mäkinen et al, 2006;Shikano et al, 2010;DeFaveri et al, 2012;Fig. 1).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…These results align with the interpretation that populations in finite and often very small freshwater habitats exhibit smaller effective population sizes than those living in marine habitats where populations are also connected by at least occasional gene flow. It is noteworthy that the polarized patterns of genetic variability and differentiation in freshwater vs marine habitats cannot be explained by biased representation (e.g., differences in key life history traits influencing genetic variability) of species in each of these groupings; similar results are seen when populations of the same species residing in freshwater and marine habitats are compared (Mäkinen et al, 2006;Shikano et al, 2010;DeFaveri et al, 2012;Fig. 1).…”
Section: Introductionsupporting
confidence: 61%
“…For instance, in spite of severely reduced genetic variability in isolated pond populations of nine-spined sticklebacks in Fennoscandia (Shikano et al, 2010), these populations show evidence for a high degree of parallel evolution in multiple phenotypic traits, apparently in response to lack of predation (reviewed in Merilä, 2013). Likewise, mosquitofish (Gambusia hubbsii) populations subject to strong genetic drift and low genetic variability (Shugg et al, 1998) show parallel adaptation in response predator mediated selection (Langerhans et al, 2007).…”
Section: Evolution In Small Populations -The Paradoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine-spined stickleback in the Baltic Sea has been shown to consist of one western and one eastern lineage meeting roughly at the entrance of the Baltic Sea (Shikano et al 2010;Teacher et al 2011), as previously also shown for cod (Nielsen et al 2003) and the bivalve Macoma balthica (Luttikhuizen et al 2012). A more extreme example of transition zones is represented by the blue mussel, where the species M. trossulus, native to the Baltic Sea is hybridized with M. edulis (Riginos and Cunningham 2005).…”
Section: Potential Causes Of Variability Patternsmentioning
confidence: 99%
“…2; Table S2a-g) coincide with a sharp salinity gradient and reduced water circulation in the Danish belts (HELCOM 2010;Johannesson and André 2006;Johannesson et al 2011). This shared genetic barrier is now supported by a wide range of fish species, such as the sand goby (Larmuseau et al 2009), sprat (Limborg et al 2009), herring (Limborg et al 2012;Lamichhaney et al 2012), whitefish (Olsson et al 2012a) and sticklebacks (Shikano et al 2010;. The relatively large genetic differentiation in this region has generally been attributed to selection for the low saline environment followed by adaptive divergence and subsequent reduced gene flow which affect selected as well as Biodivers Conserv (2013) 22:3045-3065 3059 putatively neutral genetic markers, in species with a marine background (Limborg et al 2012;Teacher et al 2013;.…”
Section: Genetic Divergence Between the Atlantic And The Baltic Seamentioning
confidence: 99%